Impact of the adolescent pertussis booster dose on the incidence of pertussis in British Columbia and Quebec, Canada. Issue 3 (16th January 2020) - Brousseau, Nicholas; Skowronski, Danuta M.; Bellemare, David; Amini, Rachid; Joffres, Yayuk; Clarke, Quinten; Quach, Caroline; Rallu, Fabien; Hoang, Linda; De Serres, Gaston
Highlights: The Tdap booster program reduced pertussis incidence among teens 15–19-years-old. The absolute impact of the Tdap program on disease burden was likely minimal. Recent signal of short-lived Tdap booster-dose effectiveness among aP-primed individuals. Abstract: Impact of an adolescent tetanus toxoid, reduced diphtheria toxoid, and acellular pertussis (Tdap) vaccine program was assessed in the provinces of British Columbia and Quebec, Canada. In both provinces, the Tdap booster has been in place since 2004, targeting Grade 9 students (14–15-years-of-age). Incidence rate ratios (IRRs) standardizing notification rates among teens 15–19-years-old to infants <1-year-old decreased following introduction of the Tdap program and were significantly halved during the 2009–2012 post-Tdap versus 2000–2003 pre-Tdap period. This program impact, however, is tempered by the observation that pertussis incidence among 15–19-year-olds was already lower than any other pediatric age group, following gradual decline from pre-teen rates even before the Tdap program. The risk of hospitalization among adolescents 15–19-years-old was also low throughout at <1/100, 000. Furthermore, IRRs increased in 2013–2017 when an increasing proportion of 15–19-year-olds were primed with acellular pertussis vaccine only, suggesting short-lived Tdap booster-dose effectiveness that warrants further monitoring.